The importance of not being earnest : the role of irreverence in philosophy and moral education - Miller, Stephen Kekoa (Array, 2019)
Plato claims that “philosophy begins in wonder” (Theaetetus, 155c–d). To genuinely question the unquestioned opens a hole in the floor of certainty. This feeling (awe and wonder may be some of the hardest emotions to invoke) is the prerequisite to true philosophical thinking. However, paradoxically, it is often the absence of irreverence that prevents true awe. In order to provoke moral seriousness in students, it is common to inadvertently “flatten” the moral world by injecting seriousness into everything; however, when everything is serious, nothing is serious. This paper explores the role of conceptual and tonal irreverence, and situates this topic more generally within the role of humor in pedagogy. Finally, the presentation demonstrates connections to social justice and the ways that educational reform, in flattening the moral world, have omitted the opportunity to generate wonder and reverence.